How does student educational background affect transition into the first year of veterinary school? Academic performance and support needs in university education - Rutland, Catrin S.; Dobbs, Heidi; Tötemeyer, Sabine (University of Toronto Press, 2016)
The first year of university is critical in shaping persistence decisions (whether students continue with and complete their degrees) and plays a formative role in influencing student attitudes and approaches to learning. Previous educational experiences, especially previous university education, shape the students’ ability to adapt to the university environment and the study approaches they require to perform well in highly demanding professional programs such as medicine and veterinary medicine. The aim of this research was to explore the support mechanisms, academic achievements, and perception of students with different educational backgrounds in their first year of veterinary school. Using questionnaire data and examination grades, the effects upon perceptions, needs, and educational attainment in first-year students with and without prior university experience were analyzed to enable an in-depth understanding of their needs. Our findings show that school leavers (successfully completed secondary education, but no prior university experience) were outperformed in early exams by those who had previously graduated from university (even from unrelated degrees). Large variations in student perceptions and support needs were discovered between the two groups: graduate students perceived the difficulty and workload as less challenging and valued financial and IT support. Each student is an individual, but ensuring that universities understand their students and provide both academic and non-academic support is essential. This research explores the needs of veterinary students and offers insights into continued provision of support and improvements that can be made to help students achieve their potential and allow informed "Best Practice".